Huntington's disease: novel therapeutic perspectives hanging in the balance. (4th May 2018) - Saavedra, Ana; García-Díaz Barriga, Gerardo; Pérez-Navarro, Esther; Alberch, Jordi
ABSTRACT: Introduction : Huntington's disease (HD), an autosomal dominant neurodegenerative disorder caused by an expansion of CAG repeats in the huntingtin gene, has long been characterized by the presence of motor symptoms due to the loss of striatal projection neurons. Cognitive dysfunction and neuropsychiatric symptoms are also present and they occur in the absence of cell death in most mouse models, pointing to neuronal dysfunction and abnormal synaptic plasticity as causative mechanisms. Areas covered : Here, we focus on those common mechanisms altered by the presence of mutant huntingtin affecting corticostriatal and hippocampal function as therapeutic targets that could prove beneficial to ameliorate both cognitive and motor function in HD. Specifically, we discuss the importance of reestablishing the balance in (1) synaptic/extrasynaptic N -methyl-D-aspartate receptor signaling, (2) mitochondrial dynamics/trafficking, (3) TrkB/p75 NTR signaling, and (4) transcriptional activity. Expert opinion : Mutant huntingtin has a broad impact on multiple cellular processes, which makes it very challenging to design a curative therapeutic strategy. As we point out here, novel therapeutic interventions should look for multi-purpose drugs targeting common and early affected processes leading to corticostriatal and hippocampal dysfunction that additionally operate in a feedforward vicious cycle downstream the activation of extrasynaptic N -methyl-D-aspartate receptor.